PERENCANAAN KOMUNIKASI KEMENTERIAN PUPR BPPW RIAU DALAM MENSOSIALISASIKAN PEMBANGUNAN INSTALASI PENGOLAHAN AIR LIMBAH (IPAL) KOTA PEKANBARU - Aprilia, Faisha Aprilia; ', Yasir (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Sosial dan Ilmu Politik, 2024)
This infrastructure development aims to improve community sanitation services and reduce environmental pollution caused by domestic wastewater which is discharged directly into rivers and land. The PUPR Ministry of Riau Province took steps, namely by carrying out outreach with the target being all Pekanbaru city residents who are around the road that will be demolished for the continuity of the WWTP project. This research aims to find out how the communication planning of the PUPR Ministry of Riau Province is in socializing the construction of a Wastewater Treatment Plan (WWTP) in the city of Pekanbaru. This research uses qualitative research methods by presenting descriptive analysis by describing the subject and object of research based on visible facts. The location of this research was carried out in Pekanbaru City, precisely at the Ministry of PUPR, Directorate General of Human Settlements, where the construction of a Wastewater Treatment Plan (WWTP) in Pekanbaru City has been carried out. Data collection techniques include interviews, observation and documentation. Data analysis techniques include data reduction, data presentation, and drawing conclusions. To check the validity of the data, triangulation is used. The results of this research are an analysis of the PUPR Ministry's problem in constructing IPALs because the density of settlements in Pekanbaru City is currently congested so that it can pollute groundwater from domestic waste which is feared to be consumed again by the community. Messages and media from communication planning in the socialization of IPAL construction are messages that are informative, persuasive and educative. Evaluation of communication planning in the socialization of IPAL development is carried out in two stages, namely internal and external evaluation. Keywords : communication, communication planning, communication development, Socialization.